A systematic review of the influence of religiosity on the adoption of an active lifestyle - Ana Raquel Mendes dos Santos; Penélopy Dabbicco; Hemília Gabrielly de Oliveira Cartaxo; Emília Amélia Pinto Costa da Silva; Maíra da Rocha Melo de Souza; Clara Maria Silvestre Monteiro de Freitas (Universidade de Fortaleza, 2014)
Objectives: To identify and analyze the determining religious factors in the adoption of an active lifestyle through a systematic review. Methods: The research was performed in the LILACS, MEDLINE / PubMed, SciELO, CINAHL, SPORTDiscus and SocINDEX databases using the following descriptors and keywords: "religion", "religiosity", "spiritual", "spirituality", "physical activity" and "physical exercise". The selection of articles had the following inclusion criteria: fully available original articles published between 2002 and 2011 in Portuguese and English. Literature reviews, theses, dissertations and monographs were excluded. Results: The sample consisted of ten articles. It could be identified from their analysis that in groups based on faith, holy scriptures and/or sacred teachings, the messages transmitted by the religious leaders and the level of religiosity are the main factors for adopting an active lifestyle. Conclusion: Religiosity appeared as an important aspect for the incorporation of physical activity in one's life, thus improving their quality of life. doi:10.5020/18061230.2013.p419